APPROACHES TO PRUDENTIAL REGULATION OF THE BANKING SECTOR TAKING INTO ACCOUNT THE CLUSTER DISTRIBUTION ACCORDING TO BUSINESS MODELS OF BANKS - Рудевська, Вікторія (Socio-economic relations in the digital society, 2020)
The analysis of the bank’s business model is an important tool for regulators and controlling bodies to detect excessive accumulation of risk on the system level over the certain period of time. Prior to the crisis, supervisory authorities concentrated on whether institutions met the level of minimum regulatory requirements and focused on external vulnerabilities, such as macroeconomic issues and financial market risks. The crisis has revealed that certain characteristic of business models has been one of the main causes of the shock, theweaknesses of the business model have become key factors in the loss of stability of banks. The traditional approach to prudential supervision is currently insufficient and requires changes that will allow supervisory authorities to assess the viability and sustainability of the business model at an early stage and identify key vulnerabilities that could ultimately lead to the failure of bank stability. The article considers the approaches to determining the business model of the bank. There is no single and objective approach to the classification of business models. Agreeing on such a classification would be the first step towards creating a proportionate approach. The article focused the influence of the business model of the bank on the key indicators of its activity is investigated; in particular on capitalization, liquidity management, profitability and credit and investment risks. The necessity of introduction of changes to the prudential supervision of the regulator on the basis of the proportional principle on the selected clusters is proved. The study concluded that each group of business models is exposed to approximately similar risks. When introducing prudential requirements, taking into account the specific characteristics of the cluster, such risks can be detected and minimized at an early stage of regulation. The principle should provide additional means to diagnose and prevent the consequences of reducing the financial stability of the bank.
Keywords: bank business model; сluster; сommercial banks; national bank; bank regulation; capital requirements